FOODBANK BROADCASTING FOR ANDROID - Nur Aina Athirah, Rusdi (Universiti Malaysia Sarawak (UNIMAS), 2019)
Foodbank is an organization that helps students in needs. This project is a way to decrease food waste by announcing information by using mobile applications. Broadcasting systems is used every day. This mobile application is to deliver information that focuses on the Foodbank. Rather than using one broadcasting system that delivers many topics of information, it is better to focus on only one type of topics so users can alert with the information without miss the important information. Broadcasting system help users to communicate with other users so they can ask any information regarding the Foodbank.